Neutrophils and Activated Macrophages Control Mucosal Immunity by Proteolytic Cleavage of Antileukoproteinase - Vandooren, Jennifer; Goeminne, Pieter; Boon, Lise; Ugarte-Berzal, Estefania; Rybakin, Vasily; Proost, Paul; Abu El-Asrar, Ahmed M.; Opdenakker, Ghislain (Frontiers in Immunology, 2018)
Antileukoproteinase or secretory leukocyte peptidase inhibitor is a small protein which protects the mucosal linings against excessive proteolysis, inflammation, and microbial infection. We discovered that gelatinase B or matrix metalloproteinase (MMP)-9, a secreted zinc-dependent endopeptidase typically found at sites of inflammation, destroys antileukoproteinase by cleavages within both of its two functional domains: the anti-microbial N-terminal and the anti-proteolytic C-terminal domains. Cleaved antileukoproteinase possessed a significantly lower ability to bind lipopolysaccharides (LPS) and a reduced capacity to inhibit neutrophil elastase (NE) activity. Whereas intact antileukoproteinase repressed proinflammatory transcript [prostaglandin-endoperoxide synthase 2 (PTGS2) and IL6] synthesis and protein secretion [e.g., of MMP-9] in human CD14+ blood monocytes stimulated with LPS, this effect was reduced or lost for cleaved antileukoproteinase. We demonstrated the in vivo presence of antileukoproteinase cleavage fragments in lower airway secretions of non-cystic fibrosis bronchiectasis patients with considerable levels of neutrophils and, hence, elastase and MMP-9 activity. As a comparison, other MMPs (MMP-2, MMP-7, and MMP-8) and serine proteases (NE, cathepsin G, and proteinase 3) were also able to cleave antileukoproteinase with similar or reduced efficiency. In conclusion, in specific mucosal pathologies, such as bronchiectasis, neutrophils, and macrophage subsets control local immune reactions by proteolytic regulation, here described as the balance between MMPs (in particular MMP-9), serine proteases and local tissue inhibitors.